2020
DOI: 10.25259/ijmio_6_2020
|View full text |Cite
|
Sign up to set email alerts
|

Study on mRNA expression of Cajal body – Gemini of coiled body proteins in head and neck squamous cell carcinoma

Abstract: Objectives: The role of proteins of Cajal bodies (CB) and its identical twin, Gemini of coiled bodies (GEMs) in maintaining genomic integrity and its influence on the initiation, progression, and prognosis of head and neck squamous cell carcinoma (HNSCC) is gaining attention. We attempted to identify the CB and GEM-associated proteins (CB-GEMs) expression in HNSCC patients and study the influence of gender, TP53 mutation, age, and tobacco use on such expression. Material and Methods: TP53 mutation, tobacco u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…In the occurrence and development of HNSCC, many oncogenes and tumor suppressor genes play a key role in it, which is helpful for the early diagnosis and treatment strategy formulation and prognosis evaluation of patients with head and neck malignancies, especially HNSCC. It is expected to improve the survival rate of patients (1)(2)(3).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the occurrence and development of HNSCC, many oncogenes and tumor suppressor genes play a key role in it, which is helpful for the early diagnosis and treatment strategy formulation and prognosis evaluation of patients with head and neck malignancies, especially HNSCC. It is expected to improve the survival rate of patients (1)(2)(3).…”
Section: Introductionmentioning
confidence: 99%
“…Zhang HD found that miR-17-5p and miR-20a negatively regulate the translation of cyclin D1, and inhibit cells from entering the S phase, thereby inhibiting the proliferation of breast cancer cells and acting as tumor suppressor genes (1). Thavarajah R evaluated the effect of miR-20a on the invasion and migration of oral squamous cell carcinoma cells through CCK-8, Transwell and scratch experiments and found that the expression of miR-20a was down-regulated; after up-regulating the expression of HPV-16E7, the expression of miR-20a increased (2). Azimi studied the role of miR-20a in oral squamous cell carcinoma and found that HPV16E7 inhibited the proliferation, invasion and metastasis of oral squamous cell carcinoma by up-regulating the expression of miR-20a (3).…”
Section: Introductionmentioning
confidence: 99%